La diffusion de Flaubert en Allemagne, traductions contemporaines (2006-2018) - Aurélie Barjonet (Flaubert: Revue Critique et Génétique)
After having published several articles on how German-speaking writers and critics appreciated Flaubert during his lifetime and then in the twentieth century, Aurélie Barjonet is continuing her research on the perception of Flaubert – concentrating only on the translations of his work between 2006 and 2018. This is the opportunity to establish a detailed inventory of the German translations of Flaubert’s work in order to distinguish between previous and new translations and to study Flaubert’s new translators.